Karakteristik Mutu Pakan Ikan Gurami (Osphronemus goramy) Pada Perbandingan Variasi Limbah Organik - Manurung, Ridho Al-Falah; Sadyasmara , Cokorda Anom Bayu; Triani, I Gusti Ayu Lani (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2024)
Fish feed is an important aspect of fish farming and a source of energy to support growth in fish. As commercial feed is still relatively expensive for farmers, organic waste can be an environmentally friendly, valuable alternative as fish feed. The organic waste used in this study concist of fish bone meal, coconut pulp, and rice bran. This study aims to determine the effect of organik waste variations on the quality characteristics of gourami fish feed and to identify the best variation according to SNI 7473-2009 and approaching characteristic of the control feed. This study used a Randomized Group Design (RBD) with 1 factor, which is the variation in the ratio of organic waste with 5 levels: fish bone meal (TI) 50% coconut pulp (AK) 15% rice bran (B) 35%, TI 60% AK 10% B 30%, TI 70% AK 5% B 25%, TI 80% AK 5% B 15%, and commercial feed (Control). he observed variables include protein content, fat, moisture, ash, crude fiber, carbohydrates, and feed diameter. The results showed that variations in the ratio of organic waste had a significant effect on the protein, fat, moisture, ash, crude fiber, carbohydrate and feed diameter, with the tested met the requierements of SNI 7473 (2009). The best treatment that produced variations that match the characteristics of SNI 7473 (2009) and close to the control was TI 80% AK 5% B 15% with characteristic values of protein content 21.29%, fat 10.61%, water 8.67%, ash 12.82%, crude fibre 22.3%, carbohydrate 46.60%, and feed diameter 5.20 mm.